(untitled) (Journal of Engineering, 2023)
To achieve sustainability, use waste materials to make concrete to use alternative components and reduce the production of Portland cement. Lime cement was used instead of Portland cement, and 15% of the cement’s weight was replaced with silica fume. Also used were eco-friendly fibers (copper fiber) made from recycled electrical. This work examines the impact of utilizing sustainable copper fiber with different aspect ratios (l/d) on some mechanical properties of high-strength green concrete. A high-strength cement mixture with a compressive strength of 65 MPa in line with ACI 211.4R was required to complete the assignment. Copper fibers of 1% by volume of concrete were employed in mixes with four different aspect ratios (20, 40, 60, and 120). At 7, 28, and 60 days after typical curing, the samples’ mechanical characteristics (compressive strength, flexural strength, and split tensile strength) are assessed. A reported increase in compressive strength of (2, 1.6, and 1.4) in (7, 28, and 60 days) for concrete with a high aspect ratio 120, compared to concrete with a low aspect ratio 20. The flexural strength of high-strength green concrete with fibers of a higher aspect ratio 120 was (23, 11, and 12.6%) times higher for all ages compared to low aspect ratio 20. The split tensile strength rose (1.7, 1.5, and 1.6%) for (7, 28, and 60 days), respectively, for concrete with a high aspect ratio 120, compared to concrete with a low aspect ratio 20. It was found that using fibers with a large aspect ratio improved the mechanical properties of concrete more than fibers with a small aspect ratio.